Needs analysis on English Online Learning in Informatics Technology Department, State Polytechnic of Malang - Satrio Binusa Suryadi (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2021)
Online learning in Indonesia gets in the position for all tertiary education levels since the established emergency curriculum set by the ministry of education and culture as the response to the global strike of of Covid-19. Online learning also applies to the State Polytechnic of Malang. As the student is familiar with conventional learning, to minimize the gap, the need analysis is taken to explore that the existing teaching and learning activities based on the student perspective. This study aims to discover the student's needs in online learning and collect some responses as the consideration to design appropriate learning activities. The study employed an online survey that taken the English for Job Preparation subject. The online survey consists of sets of questions related to learning sources, activities, and assignments. The result showed that the learning activities and materials for English subjects are required an update to get the precise learning outcomes reflecting on learner's needs as the basis for the course design.